Interrogating Okooro Masquerade: A Structuralists Reading of the Costumes - Segun Omosule (Yoruba Studies Review)
There is a gulf between the script and the artist's intention when analyzing indigenous festivals. The task confronting a critic is to isolate the artist's intention and navigate the sea of esoteric through the available tools. This difficulty specifically confronts the interpretation of indigenous masquerades. While deploying structuralism and aesthetics, the endeavor is to attempt an explication of the text through eclecticism. An honest critic will quickly resort to eclecticism-which is the deployment of tools depending on the capability of yielding meaning. This study does not find it out of place to dine with the structuralist model with special attention on the synchronic dimension of meaning while exploring aesthetics at the same time. With the help of eclecticism, the study situates masquerades within entertainment and concludes that indigenous attempts at providing pleasure must have informed the emergence of masquerades.